PENGARUH PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Veny Mayasari; Harmoni Harmoni (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
The stock price is the price that is formed according to supply and demand in the stock market and is usually in the form of a closing price or known as the closing price. Stock prices are influenced by many factors, both micro and macroeconomic. For this reason, it is necessary to do research on the factors that affect stock prices. The aim of this research is to find out how much influence sales growth and liquidity have on stock prices in manufacturing companies, various industrial sectors listed on the Indonesia Stock Exchange for the 2015-2019 period. Data collection techniques are carried out with documents, namely by downloading the financial statements of manufacturing companies in the various industrial sectors from 2015 to 2019 and then further processing them to be used as research samples. The population in this study found 24 companies and 9 samples of manufacturing companies in the various industrial sectors. The results of this study indicate that the coefficient of determination (R square) is 0.116 or 11.6%, meaning that the effect of sales growth (X1) and liquidity (current ratio) (X2) on stock prices (Y) is 11.6% while the rest is 88.4% is influenced by other variables not mentioned in this research model. The statistical results also show that sales growth (X1) partially has no significant effect on stock prices (Y), liquidity (current ratio) (X2) partially has a significant effect on stock prices (Y). Simultaneously, sales growth (X1) and liquidity (current ratio) (X2) have no significant effect on stock prices (Y). This can be proven through the F statistical test, where F. sig 0.074 (7.4%) which means the value is greater than the significance level of 0.05 (5%) then accepts H0 and rejects Ha.